Caregiver feeding practices and child weight outcomes: a systematic review - Spill, Maureen K; Callahan, Emily H; Shapiro, Myra J; Spahn, Joanne M; Wong, Yat Ping; Benjamin-Neelon, Sara E; Birch, Leann; Black, Maureen M; Cook, John T; Faith, Myles S; Mennella, Julie A; Casavale, Kellie O (The American journal of clinical nutrition, 2019)
As part of the USDA–Department of Health and Human Services Pregnancy and Birth to 24 Months Project, we conducted systematic reviews (SRs) on topics important for health and nutrition of young children. The purpose of the present SR was to examine the relation between caregiver feeding practices in children from birth to 24 mo and child weight gain, size, and body composition. A search of articles published from January 1980 to January 2017 in 4 databases identified 8739 references. Nutrition Evidence Systematic Review (NESR) analysts used the Nutrition Evidence Library Risk of Bias Assessment Tool to assess potential bias in the studies, and a Technical Expert Collaborative graded the body of evidence using the NESR grading rubric. Twenty-seven articles were included in this review (8 controlled trials, 19 longitudinal cohort studies). Moderate evidence from randomized controlled trials suggests that providing responsive feeding guidance to teach mothers to recognize and respond appropriately to children's hunger and satiety cues can lead to “normal” weight gain and/or “normal” weight status in children aged ≤2 y compared with children whose mothers did not receive responsive feeding guidance. Moderate evidence from longitudinal cohort studies indicates an association between maternal feeding practices and the child's weight status and/or weight gain, but the direction of effect has not been adequately studied. Restrictive feeding practices are associated with increased weight gain and higher weight status, and pressuring feeding practices are associated with decreased weight gain and lower weight status. Evidence suggests that a mother's feeding practices are related to concerns about her child's body weight. This review highlights the importance of the interaction between caregivers and infants and toddlers related to child feeding practices on children's weight outcomes. Research is needed on more diverse populations with consistent methodological app-roaches and objective measures.